Angiotensin II, blood–brain barrier permeability, and microglia interplay during the transition from pre-to hypertensive phase in spontaneously hypertensive rats - Makuch-Martins, Mariana; Vieira-Morais, Camilla G.; Perego, Sany M.; Ruggeri, Adriana; Ceroni, Alexandre; Michelini, Lisete C. (Frontiers in Physiology, 2024)
Background: Hypertension is characterized by upregulation of the renin-angiotensin system, increased blood-brain barrier (BBB) permeability and microglia activation within autonomic nuclei and an intense sympathoexcitation. There is no information on the interplay of these events during the development of neurogenic hypertension. We sought now to identify the interaction and time-course changes of Ang II availability, barrier dysfunction, microglia activation and autonomic imbalance within autonomic areas during the development of neurogenic hypertension. Methods: Sequential changes of hemodynamic/autonomic parameters, BBB permeability, microglia structure/density (IBA-1) and angiotensin II (Ang II) immunofluorescence were evaluated within the paraventricular hypothalamic nucleus, nucleus of solitary tract and rostral ventrolateral medulla of Wistar and spontaneously hypertensive rats (SHR) aged 4, 5, 6, 8 and 12 weeks. Somatosensory cortex and hypoglossal nucleus were also analyzed as non-autonomic control areas. Results: Augmented brain Ang II availability (4th-5th week) was the first observed change followed by the incipient BBB leakage and increased microglia density (6th week). From 5th-6th week on, BBB leakage, Ang II and IBA-1 densities augmented continuously allowing a parallel increase in both Ang II-microglia colocalization and the transition of microglial cells from highly ramified in the basal surveillant condition (4th-5th week) to shorter process arbors, fewer end points and enlarged soma in the disease-associate condition (6th up to 12th week). Simultaneously to increased Ang II-microglia colocalization and microglia morphologic phenotype changes, sympathetic activity and pressure variability augmented, autonomic control deteriorated and blood pressure increased. These responses were not specific for autonomic nuclei also occurring with lower magnitude in somatosensory cortex and hypoglossal nucleus, indicating the predominance of hypertension-induced effects on autonomic areas. No changes were observed in age-matched controls in which Ang II density did not change. Conclusions: Brain Ang II density is the initial stimulus to drive coordinated changes on BBB permeability and microglial reactivity. Increased BBB dysfunction, allowing the access of plasma Ang II, augments its local availability, the colocalization and activation of microglial cells, being a potent stimulus to increase vasomotor sympathetic activity, autonomic imbalance and pressure elevation during the establishment of hypertension.